Enhancing Elementary School Students’ Abstract Reasoning in Science Learning through Augmented Reality-Based Interactive Multimedia - Syawaludin, A.; Gunarhadi, G.; Rintayati, P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Elementary school students’ rational skill is terminated on concrete situations; therefore, enhancing abstract reasoning becomes a prompt for students to be more critical in solving science problems. The objective of the study was to improve abstract reasoning in science learning using interactive multimedia based on augmented reality (AR) for fifth-grade students. This study used a Classroom Action Research conducted in two cycles consisting of Plan, Act & Observe, and Reflect stage each. Data collection techniques used tests and observations involving 28 students. The credibility of the research data was examined based on technical triangulation and source triangulation while the collected data were analyzed descriptively. The results of the study on process aspect showed that the use of interactive multimedia based on augmented reality gave positive changes to the learning processes on earth and rock structure topic in the fifth grade of elementary school. The students’ enthusiasm during the learning processes thus strengthened student-teacher interaction as they enjoyed the learning processes actively, independently, and collaboratively. The interactive multimedia based on augmented reality facilitates the students to reason by exploring more realistic visual objects to eases student understanding of science concept, associating inter-concepts and implementation of information analysis, and problem-solving. The success of the product showed that students’ abstract reasoning in science learning enhanced by 24.20% (in the first cycle) and 23.08% (in the second cycle). The results of this study concluded that the use of interactive multimedia based on augmented reality could enhance abstract reasoning skill of the fifth-grade elementary school students.